Analysis of User Satisfaction of Electronic Medical Record (EMRE) Application Using Pieces Framework Method at Kamaipura Community Health Center, Sigi Regency - Ince Rahmi; Budiman; Ahmad Yani (PT. Anagata Sembagi Education, 2026)
The implementation of Electronic Medical Records (EMR) is mandated by Minister of Health Regulation No. 24 of 2022, but its implementation at the Kamaipura Community Health Center still faces technical obstacles such as slow internet connection and incomplete reporting features. This study aims to analyze the level of satisfaction of EMR application users using the PIECES Framework method (Performance, Information, Economic, Control, Efficiency, and Service) at the Kamaipura Community Health Center, Sigi Regency. This type of research is quantitative with a questionnaire instrument distributed to health workers (doctors, nurses, midwives, and medical records officers). Data analysis used multiple linear regression tests to determine the partial (t-test) and simultaneous (f-test) effects of PIECES variables on user satisfaction. The results showed that all PIECES Framework variables simultaneously have a significant influence on user satisfaction of the EMR application. Partially, only system reliability (performance) had a significant effect on the perception of health worker satisfaction, while information quality, economic, control/security, efficiency, and service showed no significant partial effect. It can be concluded that the PIECES method is effective in mapping weaknesses in the EMR system. The recommendations of this research are the need to increase internet network capacity, complete reporting features, and prepare official SOPs.